2005
DOI: 10.1021/bi050141j
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Sortase Transpeptidase SrtA:  Insight into the Kinetic Mechanism and Evidence for a Reverse Protonation Catalytic Mechanism

Abstract: The Staphylococcus aureus transpeptidase SrtA catalyzes the covalent attachment of LPXTG-containing virulence and colonization-associated proteins to cell-wall peptidoglycan in Gram-positive bacteria. Recent structural characterizations of staphylococcal SrtA, and related transpeptidases SrtB from S. aureus and Bacillus anthracis, provide many details regarding the active site environment, yet raise questions with regard to the nature of catalysis and active site cysteine thiol activation. Here we re-evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
189
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 61 publications
(102 reference statements)
12
189
1
Order By: Relevance
“…Slightly higher substrate concentrations (2.7 mM) were used than would ideally be the case; however, given the low levels of activity of several of the enzymes being measured, it was necessary to use low millimolar concentrations of substrate in order to obtain detectable levels of product using our HPLC-based assay. (33,39). By contrast, SrtB had no detectable activity against the LPETG substrate, even after 12 h at 37°C and an enzyme concentration of 94.8 M. This is consistent with earlier studies in which no LPETG-cleaving activity was observed for SrtB in vitro (22).…”
Section: Motifsupporting
confidence: 91%
See 1 more Smart Citation
“…Slightly higher substrate concentrations (2.7 mM) were used than would ideally be the case; however, given the low levels of activity of several of the enzymes being measured, it was necessary to use low millimolar concentrations of substrate in order to obtain detectable levels of product using our HPLC-based assay. (33,39). By contrast, SrtB had no detectable activity against the LPETG substrate, even after 12 h at 37°C and an enzyme concentration of 94.8 M. This is consistent with earlier studies in which no LPETG-cleaving activity was observed for SrtB in vitro (22).…”
Section: Motifsupporting
confidence: 91%
“…3). For comparison, previous studies have reported a k cat of 0.28 Ϯ 0.02 s Ϫ1 for SrtA ⌬N24 and a K m of 7.3 Ϯ 1 mM for SrtA ⌬N24 with Abz-LPETG-Dap(DNP)-NH 2 (39). These values show that SrtB has a K m for this substrate that is within the error of that measured for SrtA but a k cat that is ϳ500-fold lower.…”
Section: Motifsupporting
confidence: 51%
“…15 Nfiltered (F2) 13 C-edited NOESY-HSQC and (F1) 13 C, 15 N-filtered (F2) 15 N-edited NOESY-HSQC (30), and two-dimensional (F1) 13 C-filtered NOESY spectra (29). The majority of and dihedral angle restraints were obtained using the program TALOS (31).…”
Section: Cmentioning
confidence: 99%
“…Additional angle restraints were obtained by measuring 3 J HN␣ values from HNHA spectrum (32), and additional angle restraints were obtained by analyzing threedimensional 15 N-edited NOESY spectrum (33). 1 angles for dihedral angle restraints and stereotypical chemical shift assignments of ␤-methylene protons were obtained by analyzing 15 N-TOCSY-HSQC, HNHB, HN(CO)HB, and 15 N-ROESY spectra (34,35).…”
Section: Cmentioning
confidence: 99%
See 1 more Smart Citation